A nagy átalakulás Budapest környékén a 19–20. században. Egy empirikus társadalomtörténeti kutatás tapasztalatai - Kiss, József (Tér és Társadalom, 1990)
Basic conditions of capitalism developed in the northern and southern surroundings of Pest during the three decades between 1860-1890. These conditions were protection against floods, development of road and railroad networks taking industrial rationalizations into account as well, formations of settlements with planned, functional basic structure and modernization of administration. Development of the neighbouring area south of Budapest was delayed with a good 20-30 years as compared to the northern region. The typical seftlement and socio-structural phenomenon, "the city and its surroundings" was the direct consequence of intensive, American-type industrialization. In this context the "city" is practically the seftlement created in 1873, which developed seperately within its limits. At the same time, the "surroundings" settled down and became an organic part of the city in two different rings. One of the rings was a dense, internal ring of settlements located around the urban core and later they formed a complete seftlement. The other ring was a more dispersed external one, which was called then the rural protective ring of the city. Villages in the sphere of influence of large cities usually have two faces: on the one hand, the face of independent (autonomous) settlement, and on the other, the residential (peripheric) character related to the city. Nearness of urban development energies, their structure and dynamism exert pressure and attraction at the same time. This basic situation became permanent in the relationship – often burdened with conflicts – of the city and its surroundings until as late as 1950, the year of unification.